The syntheses, structure and properties of cobalt complexes with beta-alanine derivatives - YALÇIN, BAHATTİN (PERGAMON-ELSEVIER SCIENCE LTD, 2006)
N-(2-hydroxynaphtalidene)beta-alanine (I) forms two type complexes with Co(II) ions: binuclear complex [CO2(Nap beta ala)(2)(.)2H(2)O](H2O)-H-. (III) and trinuclear mixed-valence complex {[Co(Nap beta ala)(2)](2)Co-.(H2O)(4)}(.)4H(2)O(.)2C(2)H(5)OH (IV). X-ray data and magnetic measurements indicated that trinuclear complex had Co-III-Co-II-Co-III distribution of oxidation states. Co(III) ions has weak distorted octahedric environment of four oxygen and two nitrogen atoms due to two ligand molecules per each. The tetrahydrate envelope of Co(II) ion is upgraded to octahedra with two oxygen atoms of two bridge carboxylic group of the ligand molecules which coordinates Co(III) ions. The azomethine bond in I is reduced to secondary amine group by sodium borohydride in dimethylformamide solution, which contains water. Cobalt (II) complex of the reduced Schiff base Co(RNaph beta ala)(.)2H(2)O (V) has been synthesized and its spectroscopic and magnetic properties are reported. Binuclear cobalt (II) complex of Schiff base is reduced by NaBH4 and complex V is obtained. Trinuclear mixed-valence complex IV Could not be reduced under similar conditions. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: cobalt; mixed-valence complex; binuclear complex; trinuclear complex; Schiff base; beta-alanine; MOLECULAR-STRUCTURE; CRYSTAL-STRUCTURE; METAL-COMPLEXES; COPPER(II) COMPLEXES; ZINC(II); NICKEL(II); MODEL